Optimise a solar thermal cooling system using combined simulation TRNSYS and Genopt software for refrigeration demand in various African climates - Abdelwanes, Abdelsalam; King, Peter; Wijayantha, Upul K. G.; Patchigolla, Kumar; Renaldi, Renaldi (Sage, 2025)
This study presents an optimisation simulation-based approach for the ideal solar absorption cooling system design, including a thermal storage tank and a solar thermal collector. The strategy aims to reduce the costs of solar chilling systems by determining the optimal collector area and storage capacity while minimising electricity consumption to operate system. A hybrid approach is used to achieve the optimal configuration by combining dynamic simulation with TRNSYS and an optimisation algorithm using Gen-Opt. The system’s life cycle cost, over 20 years, serves as the optimisation goal. The study examines the effects of three economic factors: solar collector area, storage capacity, and electricity prices, on the design. The outcomes are analysed from technical and economic perspectives across various African locations. Additionally, techno-economic optimisation was conducted to identify the best set of system design parameters. The findings illustrate how electricity prices and climatic conditions influence the techno-economic feasibility of the system. Alkufra demonstrates and achieves the best techno-economic performance due to its high solar radiation and lower reliance on auxiliary power, which reduces electricity costs throughout the system’s lifetime. Cairo achieves a fairly reasonable performance, providing satisfactory economic viability compared to Lagos or Accra, due to sun availability and electricity costs.
Keywords: Absorption chillers; absorption refrigeration; energy storage/ auxiliary systems; solar energy systems; solar thermal conversion; 40 Engineering; 4010 Engineering Practice and Education; 4017 Mechanical engineering